Quality attribute and customer satisfaction: Using Kano's model to prioritize what matters most to customers - Norlia Ahmad (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2017)
Continuous innovations of smartphone attributes and increasing product usage call for better understanding of the attributes that matter most to customers. This study employs Kano's model for classifying smartphone attributes into various categories and examines the influence of those attributes on the satisfaction of smartphone users. Based on consumer evaluation of the latest and general smartphone attributes, the analysis in this study indicates various levels of satisfaction and dissatisfaction with each attribute. Specifically, our findings reveal merely three categories of Kano's classification, and "one-dimensional" or performance attributes have higher influence on customer satisfaction as compared with "attractive" ones. These findings provide implications for further product improvement efforts to consider not only technological capabilities but also to prioritize the attributes that are highly expected by customers. The majority of the respondents in this study include the younger consumer segment and heavy smartphone users, thus limiting generalization of the results to other contexts. Further research should consider respondents across segments and/or in a specific market, and extend the focus beyond product attributes so as to include user experiences and explicit product benefits.
Keywords: M31; M15; L96; 650; quality attribute; customer satisfaction; Kano's model; convergent product